The South African parliamentary committee system and institutional capacity - Doyle, Monique (Department of Political Studies, 2017)
This study aims to provide an analysis of the factors which facilitate or impede the capacity of the portfolio committees of the South African National Assembly in the carrying out of the primary function of oversight. Parliamentary oversight presents itself as a key function of legislatures and further than this, serves as a primary indicator of the effectiveness of the legislature as a principle institution in the system of democratic governance. There has not been much contribution to the field of study of the committee system of the South African Parliament much less its institutional capacity. The dissertation conceptualised capacity as the "hard" physical resources available to the committees as well as the "soft" political environment in which the committee operates. The study made use of a number secondary documents relating to the work of committees along with data collected from interviews carried out with chairpersons and committee researchers. From an analysis of these variables in relation to a sample of committees, findings present a varied picture where capacity, in terms of both hard and soft variables, differ from one committee to the next. Overall committees differ from one to the next whether in terms of the scope of their oversight or their workload and this study found that capacity has to mirror these distinctions for effective oversight.